IMPROVING EFFICIENCY OF THE JET PUMP AT LOW COEFFICIENTS OF EJECTION - A. G. Butenko; S. Yu. Smik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Jet pumps are widely used in the power industry as well as in many others. Their main disadvantage is low operating efficiency which aggravates when the jet pump is working with a low ejection coefficient. Such modes are sometimes unavoidable being conditioned by the character of technological process. The article considers methods of improving the operation of central ejectors at small ejection coefficients.The authors use mathematical simulation approach to study the particularities of kinematic structure of the flow in the mixing chamber of the central ejector operating with low ejection coefficients. They utilize Solid Works Cosmos Flo application-program package for the mathematical simulation. The study shows that areas of reverse flows appear alongside the walls of the mixing chamber under the above conditions which reduces the efficiency of the jet apparatus. The more is the extent of the discovered areas the more is the loss of energy. The study detects the regime zones where detached flows areas appear. The authors propose to replace such areas with solid surface (substitution bodies) for preventing them from emerging. The  mathematical  simulation  results  determine  the  geometric  parameters  of the  substitution bodies for the central ejectors with different modules and ejection coefficients and yield mathematical description of their shape. Mathematical and physical simulation of the centralejector operation with the substitution bodies shows the increase in pressure-head and efficiency coefficients in such apparatuses as compared to ejectors of the conventional form. Efficiency increase is the case in quite a wide range of operating modes.The proposed method of the efficiency increase for the central ejectors is rather straightforward and does not require substantial financial expenditures for its implementation.